Analysis of industry based microprocessor learning module design - Irwanto Irwanto (Asian Journal of Educational Technology, 2022)
The Microprocessor course is a mandatory course that must be taken by every PVTE undergraduate student, in understanding the material contained in this course, the researcher assumes to develop a learning module. The purpose of this study is to facilitate student understanding in learning microprocessor material. In this thesis research, using R&D research with the aim of developing learning media in the form of Microprocessor Course Learning Modules in order to determine the effectiveness and quality of microprocessor learning modules so as to add insight and interest in reading for 4th semester students of the PVTE Study Program, FKIP Sultan Ageng Tirtayasa University. The method used in this research is the research and development method by Sugiyono. The research stage is limited to 5 stages, namely: (1) potential and problems, (2) data collection, (3) product design, (4) product validation, and (5) trial use in order to determine the feasibility of this module learning media. The results of the development of learning media for the Microprocessor Course Module are for the results of the assessment of the media expert validator to get a percentage result of 90% where these results have entered the "very feasible" category. while for the results of the Material expert validator, the percentage result is 89%, which indicates that the content of the material in the Microprocessor Course learning module can be categorized as Very Appropriate.